Antiviral Activities of Quercetin and Isoquercitrin Against Human Herpesviruses - Chae Hyun Kim; Jung-Eun Kim; Yoon-Jae Song (Molecules, 2020)
We previously reported that the ethyl acetate (EtOAc) fraction of a 70% ethanol extract of Elaeocarpus sylvestris (ESE) inhibits varicella-zoster virus (VZV) and human cytomegalovirus (HCMV) replication in vitro. PGG (1,2,3,4,6-penta-O-galloyl-ß-D-glucose) is a major chemical constituent of the EtOAc fraction of ESE that inhibits VZV but not HCMV replication. In this study, we comprehensively screened the chemical compounds identified in the EtOAc fraction of ESE for potential antiviral properties. Among the examined compounds, quercetin and isoquercitrin displayed potent antiviral activities against both VZV and HCMV with no significant cytotoxic effects. Both compounds strongly suppressed the expression of VZV and HCMV immediate–early (IE) genes. Our collective results indicated that, in addition to PGG, quercetin and isoquercitrin are bioactive compounds in the EtOAc fraction of ESE that effectively inhibit human herpesvirus replication.